Nonverbal Communication in the Concept of Javanese Opera Film Artistic Arrangement - Heri Nugroho (CHANNEL: Jurnal Komunikasi, 2021)
The film is one of the communication media used to convey information from its creator to the audience. The film is referred to as one of the communication media. The statement that film is as its effect on the audience shows communication medium. Mainly after watching a movie, the audience will believe that the film is good or not. These events or phenomena are evidence that there is information conveyed to the audience when watching a film, whether they like or do not like it. The purpose of this study is to find a solution to the communication problem that occurs in the Javanese Opera film as a communication medium so that it can provide education, especially for film lovers, to gain insight into how to watch films like Opera Jawa. This research was carried out using qualitative research methods to obtain factual data to explain so that it was easy to deliver. After analyzing the study of nonverbal communication in the Opera Jawa film, it can be concluded that art as a form of aesthetic value and a medium of communication means communicating through beauty with a series of information packaged through visual language, making it richer and more diverse in how to communicate.